Impact Evaluation of Digitalisation and Pre-Employment Card on the Economy of West Papua - M. Rismawan Ridha (Pattimura University, 2026)
West Papua can serve as a best practice for eastern Indonesia in fostering structural transformation in national development post-Covid-19. With the highest economic growth rate (20.80 per cent) in 2024, the province has also reported an increase in the literacy of the productive-age population in information and communication technology (ICT). Nonetheless, West Papua’s digital competitiveness remains relatively low, coupled with substantial challenges in transitioning the young workforce into employment or further education, as reflected in the escalating numbers of individuals classified as Not in Employment, Education, or Training (NEET). This study seeks to examine the impact of digitalisation on economic improvement within the community and evaluate the effectiveness of the pre-employment card program in facilitating job opportunities for youth in West Papua. Employing data from the August 2021–2022 National Labour Force Survey (Sakernas) and the 2021 Village Potential Survey, the analysis utilized Instrumental Variables (IV) Two-Stage Least Squares and Propensity Score Matching (PSM) econometric methods. The results indicate a strong positive association between digitalisation and individual income, with substantially higher earnings among digitally engaged workers, conditional on observable characteristics and instrument validity assumptions. Furthermore, the PSM analysis reveals that the pre-employment card program significantly increases employment opportunities for young individuals, emphasizing the need for continued governmental support in technology access and program benefits.